Financial Feasibility Analysis of Tofu Factory Business in Tegalgondo Village, Karangploso District, Malang Regency, East Java - Maria Wini Dowa; Agnes Quartina Pudjiastuti; Nur Ida Iriani (IRDH International Journal of Social Sciences & Humanities, 2025)
This research aims to determine the financial feasibility analysis of the ADMA NU Tofu Factory located in Tegalgondo Village, Karangploso District, Malang Regency, East Java. Method: The type of research used is qualitative research, with data collection conducted through direct interviews with the owner of the ADMA NU Tofu Factory. The method of data analysis used is financial feasibility analysis for the business, which includes calculations of Net Present Value (NPV), Payback Period (PP), Internal Rate of Return (IRR), and Profitability Index (PI). The research findings indicate that ADMA NU Tofu Factory is in good financial condition and is feasible for development. The NPV of Rp. 1,269,693,712 suggests that the business generates high profits. The PP indicates a payback period of 8-9 days in 2025. The IRR of 45.75% demonstrates a high ability to return investments. The Profitability Index (PI) of 1.90 (>1) confirms that the business is in a healthy financial condition. Based on the analysis's, the financial performance of the ADMA NU Tofu Factory is deemed feasible and has good prospects for further development.